Answer:
You got it wrong. It is supposed to be (1, -4)
Explanation:
If you are not sure, just plug it in. So based on this you got that x= -6.
So plug x=-6 into the first equation. -6= -y-3. So you solve for y.
You add 3 to both sides and get that -3= -y and y=3, so you did not get it correct because you got that y=-4. So you may be asking, how do you do this?
So first, you already know that x=-y-3. So you substitute that into the 2nd equation for x. That gets you -2(-y-3)-y=2. Use distributive property and get 2y+6-y=2. Combine like terms and subtract 6 from both sides to get y= -4.
Now you substitute y=-4 into any equation, I'll just use the first equation. X= -(-4)-3. That gets x= 4-3. That gets x= 1